Impact of season and geography on CompEx Asthma: a composite end-point for exacerbations. Issue 4 (19th October 2020) - Jauhiainen, Alexandra; Scheepers, Lieke E.J.M.; Fuhlbrigge, Anne L.; Harrison, Tim; Zangrilli, James; Garcia Gil, Esther; Gustafson, Per; Fagerås, Malin; Da Silva, Carla A.
Background: CompEx Asthma, a novel composite end-point combining severe exacerbations (SevEx) with asthma-worsening events, was recently developed. Further characterisation of CompEx Asthma is needed to illustrate the applicability of this end-point. The objective was to evaluate CompEx Asthma as a rate end-point to determine how seasonal and geographical factors impact this novel outcome. Methods: Seven 24–56-week randomised controlled trials of budesonide/formoterol (BUD/FORM) and benralizumab were analysed. Annualised event rates (AERs) and treatment effects (hazard ratio (HR)) were analysed with Poisson and Andersen–Gill models, respectively. Seasonality was analysed by month and five geographical regions were evaluated. Results: The studies included 10 815 patients (63% female, mean age 42–49 years). CompEx Asthma AER mirrored seasonal variations in SevEx AER. CompEx Asthma AERs were higher versus SevEx in BUD/FORM and benralizumab trials (range 2.7–4.5-fold and 1.3–2.0-fold increase, respectively) and were less variable versus SevEx between regions (ratios of greatest:smallest AERs: 1.36 for CompEx versus 2.28 for SevEx (BUD/FORM); 1.81 for CompEx versus 2.22 for SevEx (benralizumab)). Treatment effects for CompEx Asthma and SevEx were generally similar across regions and months. However, in Eastern Europe, where SevEx rates were lowest, treatment effect was greater with CompEx Asthma versus SevEx, reaching statistical significance in the benralizumab studies (HR (95% CI): 0.67 (0.53–0.85) versus 0.87 (0.65–1.15)). Conclusion: This study confirmed the reliability of CompEx Asthma as a rate end-point and allowed detection of variations in seasonal SevEx rates, reduction of variation in rates across regions and potential greater sensitivity to treatment effects. CompEx Asthma is a valid end-point that reflects the treatment efficacy observed on SevEx when studying recurrent events and may enable smaller, 3-month clinical trials factoring in seasonal variation https://bit.ly/3jPI894